Multilaboratory evaluation of screening methods for detection of high-level aminoglycoside resistance in enterococci. National Committee for Clinical Laboratory Standards Study Group on Enterococci. - Swenson, J M (1995)
Since the early 1970s, the synergistic activity of an aminoglycoside with a cell wall-active agent has been predicted by determining the ability of an enterococcus to grow in the presence of high levels of the aminoglycoside (usually > or = 2,000 micrograms/ml). However, a variety of media and concentrations of aminoglycosides has been used for this screening procedure. In the present study, we sought to optimize the agar dilution, broth microdilution, and disk diffusion tests used to detect high-level gentamicin and streptomycin resistance in enterococci. For dilution tests, brain heart infusion agar or broth gave the best growth and performance. For agar dilution, 500 micrograms of gentamicin per ml, 2,000 micrograms of streptomycin per ml, and an inoculum of 1 x 10(6) CFU/ml were optimal, while for broth microdilution, 500 micrograms of gentamicin per ml, 1,000 micrograms of streptomycin per ml, and an inoculum of 5 x 10(5) CFU/ml were best. Growth of more than one colony in the agar dilution test was determined to be the best indicator of high-level resistance. For disk diffusion, Mueller-Hinton agar, 120-micrograms gentamicin disks, and 300-micrograms streptomycin disks with breakpoints of no zone for resistance and > or = 10 mm for susceptibility gave the best sensitivity and specificity if results for strains with zones of 7 to 9 mm are considered inconclusive, indicating that a broth or agar test should be performed to determine susceptibility or resistance.